(untitled) (Studia theodisca, 2014)
Italian scholars have been reading Hölderlin since 1915. The present contribution outlines this century of literary and philosophical criticism, with its diverse stages and its connections to the parallel histories of Italian translations and transformations of Hölderlin’s work, up to the “new wave” in our millennium.